2016
DOI: 10.4103/0970-9290.195644
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of sutures coated with triclosan and chlorhexidine for oral biofilm inhibition potential and antimicrobial activity against periodontal pathogens: An in vitro study

Abstract: The antibacterial coated sutures have a promising potential in preventing the colonization of periodontal pathogens around it thereby inhibiting biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…They can contribute to inflammatory reactions and differ between patients. [ 10 16 ] Previous studies have investigated the wicking effect of silk[ 7 17 ] and show similar results to our study. Granet et al .…”
Section: Discussionsupporting
confidence: 89%
“…They can contribute to inflammatory reactions and differ between patients. [ 10 16 ] Previous studies have investigated the wicking effect of silk[ 7 17 ] and show similar results to our study. Granet et al .…”
Section: Discussionsupporting
confidence: 89%
“…In view of the peculiarities of the oral cavity and the absence of an ideal suture the use of antimicrobial solutions for mouthwash is among the main postoperative recommendations 2 . Chlorhexidine gluconate (0.12%) is the most indicated antimicrobial because it has a broad spectrum of action 6,15 . However, the dose-response effect through indiscriminate use may affect the viability of epithelial cells and fibroblasts, interfering in the regulation of proinflammatory cytokines and growth factors, contradictorily, hindering tissue repair and increasing the resistance of microorganisms 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Some factors, such as the diversity of microorganisms, the presence of saliva, rich vascularization, contamination by food residues and trauma resulting from speech and hygiene increase the inflammatory process, the healing time and the discomfort of the patient 5 . In addition, removal of the suture in infectious areas may lead to bacteremia which is a risk factor for the development of bacterial endocarditis in high-risk patients 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Sethi et al . [17] concluded that both triclosan- and chlorhexidine-coated sutures have antibacterial property against periodontal pathogens and can have a promising role in the prevention of SSIs although it would require further in vivo validation. According to Zeiler and Grohe[18], ciprofloxacin showed rapid bactericidal action against organisms in both the logarithmic and stationary growth phases.…”
Section: Discussionmentioning
confidence: 99%